2017
DOI: 10.1002/prp2.362
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterizations of diallyl sulfide analogs for their novel role as CYP2E1 enzyme inhibitors

Abstract: Diallyl sulfide (DAS), a selective inhibitor of CYP2E1, has shown protective effects against alcohol‐ and acetaminophen‐induced hepatotoxicity in many studies. However, DAS is also a CYP2E1 substrate that on metabolism produces toxic metabolites and causes cytotoxicity. The objective of this study was to find a potent DAS analog as a CYP2E1 inhibitor and has the characteristic of producing less toxic metabolites. We selected seven commercially available compounds that are similar to DAS (DAS analogs). First, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In our laboratory, we have identified several analogs of diallyl sulfide (DAS) as more potent and relatively safer CYP2E1 inhibitors. Diallyl ether (DE) is one of the analogs with the best CYP2E1 inhibitory capacity and lowest toxicity profile 36,37 . We pretreated HepaRG cells with ALC and/or APAP and plasma exosomes with or without pre-treatment with DE.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory, we have identified several analogs of diallyl sulfide (DAS) as more potent and relatively safer CYP2E1 inhibitors. Diallyl ether (DE) is one of the analogs with the best CYP2E1 inhibitory capacity and lowest toxicity profile 36,37 . We pretreated HepaRG cells with ALC and/or APAP and plasma exosomes with or without pre-treatment with DE.…”
Section: Resultsmentioning
confidence: 99%
“…4B, *p < 0.05 compared to control scramble siRNA, ##p < 0.001 compared to ethanol scramble siRNA). Furthermore, we treated U1 cells with a novel CYP2E1 inhibitor diethyl ether (DE), which has been identified by our group [31], to further examine the role of CYP2E1 in ethanol-enhanced HIV-1 replication. As expected, selective CYP2E1 inhibitor DE significantly decreased the level of HIV-1 replication (~25%) upon ethanol exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a low molecular weight cyclic compound (TP) is expected to work as a potent inhibitor but not as a substrate due to its cyclic structure. Our inhibition study showed that two analogs (DE and AMS) were stronger CYP2E1 inhibitors than DAS, TP had a similar inhibitory capacity to DAS, and the other analogs showed moderate CYP2E1 inhibition (Rahman et al, 2017). Despite the differences in the magnitude of their inhibition, we included all seven analogs for this in vitro toxicity and efficacy study.…”
Section: Resultsmentioning
confidence: 76%
“…We hypothesize that modification of the parent DAS structure would result in analogs with improved CYP2E1 inhibition capacity and reduced cytotoxicity. In our previous study, based on a computational ligand-docking analyses, we evaluated seven structural analogs (allyl methyl sulfide, allyl ethyl sulfide, diallyl ether, thiophene, 2-(prop-2-en-1-yloxy) ethan-1-amine, 5-hexen-1-amine, and 2-prop-2-enoxyacetamide) of DAS for their CYP2E1–inhibitory properties (Rahman et al, 2017). We found that two analogs (diallyl ether and allyl methyl sulfide) had greater CYP2E1 inhibitory capacity than DAS, while other analogs showed inhibitory capacity for CYP2E1 similar to DAS.…”
Section: Introductionmentioning
confidence: 99%